Analisis Wawasan Jender Perempuan pada Perspektif Keluarga - Sumiharti Sumiharti; Sainil Amral (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this research is to describe women's gender insight from a family perspective through the characterization structure in Fira Basuki's novel Atap. This research uses descriptive qualitative research methods, solving problems in a study by describing or interpreting objects in the form of social phenomena or events that are revealed through expressions. Through this research, researchers can describe data from the object of research related to aspects of women's gender insight from a family perspective through the characterization structure in Fira Basuki's novel Atap. These aspects consist of aspects of socio-cultural change through the family and aspects of violence in the family from a feminist point of view. The source of data in this reseaech is the novel Atap by Fira Basuki. The data in this research were obtained from words, sentences, or expressions contained in the novel which refer to aspects of socio-cultural change through the family and aspects of family violence from a feminist point of view. The results showed that in socio-cultural changes through the family, it was found that there was still a gender bias towards justice that was obtained by women. Gender bias is also found in the female characters Kunti, Jane and Mak Umah as a result of violence in the family from a feminist point of view. Based on the problems that arise in socio-cultural relations through the family, it should be addressed wisely and directed in the form of protection. For example, legal protection is made and the public understands the existing forms of legal protection.